2011
DOI: 10.5424/sjar/2009072-1500
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different mulch materials in a tomato (Solanum lycopersicum L.) crop

Abstract: Black polyethylene as mulch is the most extended material among vegetable growers; however, photodegradable and biodegradable films have appeared as an alternative to conventional mulches due to the risk of the progressive contamination of soils. Reflective materials reflect back most of the incoming solar radiation, being recommended in areas characterized by high soil temperatures. We compared the effect of three mulches, black polyethylene, black biodegradable corn starch plastic and aluminized photodegrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 22 publications
0
26
0
10
Order By: Relevance
“…Kijchavengkul et al [2008] emphasize that the color of film also matterswhite biodegradable film decomposes faster than the black one. Moreno et al [2009], as well as Ngouajio et al [2008] reported that soil under black biodegradable film was less heated than in the case of black PE film, still the yield of plants mulched with those materials was comparable. The effect was confirmed in the research by Kijchavengkul et al [2008] and Anzalone et al [2010].…”
Section: Resultsmentioning
confidence: 90%
“…Kijchavengkul et al [2008] emphasize that the color of film also matterswhite biodegradable film decomposes faster than the black one. Moreno et al [2009], as well as Ngouajio et al [2008] reported that soil under black biodegradable film was less heated than in the case of black PE film, still the yield of plants mulched with those materials was comparable. The effect was confirmed in the research by Kijchavengkul et al [2008] and Anzalone et al [2010].…”
Section: Resultsmentioning
confidence: 90%
“…Generally, researchers using black plastic instead of bare soil have recorded higher yield of many crops (Ibarra et al, 2001;Kwabiah, 2004;Ban et al, 2009;Igbal et al, 2009;Mamkagh, 2009;Moreno et al, 2009;Rashidi et al, 2010;Berihun, 2011;Bhatt et al, 2011;Hatami et al, 2012;Kumar and Lal, 2012). Nevertheless, the current study aimed to investigate the effect of black polyethylene plastic mulch on okra and squash growth and yield under rain-fed conditions.…”
Section: Ajabsmentioning
confidence: 99%
“…However, new materials described in detail by Martín-Closas and Pelacho (2011) and Kasirajan and Ngouajio (2012) have appeared recently due to the nondegradability of these fi lms. Most of them demonstrated satisfactory behavior in relation to weed control and crop yields (Moreno et al, 2009;Cirujeda et al, 2012). Fruit quality infl uences the degree of acceptance of the fi nal product, so some of the aspects relating to external appearance are even more important than the price for the average consumer (Shewfelt, 1990;Gómez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%